THE IMPORTANCE AND RESULTS OF INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS - S.J. Abdiyxamidova; Sh.K. Umedov; U.A. Narzulloev (Western European Studies, 2024)
It is known that in the process of teaching physics in secondary schools, the fundamentals of scientific worldview, logical thinking, intellectual intelligence and the necessary knowledge, skills, and abilities are formed in students to continue their education. In secondary special educational institutions, this pedagogical phenomenon continues and is further developed in the process of teaching physics. Because the main goal of the physics program is to provide fundamental knowledge of general physics on the basis of general education: to show that physical theory is a generalized form of information about observations, experiments and phenomena; and by emphasizing the importance of physics in technology, technique, medicine, and personal life, it is to arouse interest in this science and create a basis for continuing its study.
Keywords: educational; emphasizing; science; medicine